Angelica archangelica subsp. littoralis (Apiaceae) – a new native taxon for Britain. (2nd January 2017) - Stroh, Peter; Scott, Walter
Abstract : Angelica archangelica is subdivided into two taxa – subsp. archangelica and subsp. littoralis . Subspecies archangelica is a cultivated introduction found across much of its northern range, including Britain and Ireland, where it is an alien species of riverbanks, roadsides and waste ground. Subspecies littoralis has a mainly native coastal distribution in Scandinavia, Germany and the Balkans, and has not previously been recorded from Britain or Ireland. However, in recent years there have been records for subsp. littoralis at three remote coastal locations in Shetland. We contend that the plants arrived and temporarily established via natural means from a native origin and consequently that A. archangelica subsp. littoralis should be recognised as a new native British taxon, albeit one that is now presumed extinct at the sole locality.